Visualizing the United States electricity-water-climate nexus. (September 2021) - Fulton, Julian; Jin, Ying
Abstract: The United States power sector uses immense quantities of water and is vulnerable to drought, water mismanagement, and climate change. Integrated management of energy and water systems is therefore critical, yet is hindered by disparate and delayed information. We present the Energy-Water-Emissions Dashboard (EWED) as an integrative modeling approach and exemplary web-based user interface displaying monthly generation, water withdrawal and consumption, and greenhouse gas emissions at nearly 10, 000 U.S. power plants from 2003 to the most recent data available. EWED users may view aggregated results at larger spatial scales including watersheds, where they are compared to modeled water availability data. EWED also models projections out to 2050 based on a range of energy and climate scenarios, finding that water resources will continue to play a critical role in energy sector transitions. As such, EWED supports efforts to integrate decision making on immediate and long-term management challenges at energy-water-climate nexus. Graphical abstract: Image 1 Highlights: Existing electricity-water assessments can be complemented by our modeling approach. Our tool shows potential water availability-based constraints on the power sector. Power sector water use has declined but is projected to increase in coming decades. Future power sector water use varies with energy sources and technologies. Our tool supports integrated energy-water management over short and long terms.